The Heme Connection: Linking Erythrocytes and Macrophage Biology - Alam, Md Zahidul; Devalaraja, Samir; Haldar, Malay (Frontiers in Immunology, 2017)
Erythroid function and development is intimately linked to macrophages. The primary function of erythrocytes is oxygen delivery, which is mediated by iron-containing hemoglobin. The major source of this iron is a recycling pathway where macrophages scavenge old and damaged erythrocytes to release iron contained within the heme moiety. Macrophages also promote erythropoiesis by providing a supportive niche in the bone-marrow as an integral component of ‘erythorblastic islands’. Importantly, inflammation leads to alterations in iron-handling by macrophages with significant impact on iron homeostasis and erythropoiesis. The importance of macrophages in erythropoiesis and iron homeostasis is well established and has been extensively reviewed. However, this developmental relationship is not one-way and erythrocytes can also regulate macrophage development and function. Erythrocyte-derived heme can induce the development of iron-recycling macrophages from monocytes, engage pattern recognition receptors to activate macrophages, and act as ligand for specific nuclear receptors to modulate macrophage function. Here we discuss the role of heme as a signaling molecule impacting macrophage homeostasis. We will review these actions of heme within the framework of our current understanding on the role of micro-environmental factors in macrophage development and function.